Does previous work experience matter in students' learning in higher project management education?. Issue 1 (19th December 2019) - Sharma, Keshav Kumar; Israel, D.; Bhalla, Bhavna
Abstract : Purpose: In view of the substantial gaps between desirable and actual competencies of project practitioners, there is a genuine and continual need to improve approaches towards project management education. The purpose of this paper is to empirically examine whether previous work experience of students pursuing a master's programme in project management plays a role in their understanding and learning from the programme. Design/methodology/approach: Survey data were collected from 282 respondents, who included working project professionals along with first-year (junior) and second-year (senior) students of a two-year postgraduate programme in project management. Considering the responses of working project professionals as the benchmark, the paper employs exploratory factor analysis and multiple comparisons to examine differences in the perceived importance given to factor groupings of critical success factors (CSFs) of construction projects by different respondent groups. Findings: Results of the study suggest that irrespective of students' seniority in the postgraduate programme, responses of students with previous project work experience more closely match the responses of project professionals, in contrast to students without such experience. The results indicate that students' previous project work experience does play a role in their understanding and learning. In addition, the paper also identifies four factor groupings of CSFs and, diverging from past studies, conceptualises "alignment" as a new factor grouping. Practical implications: Findings support the view that adequate previous work experience may be included as an essential qualifying requirement for pursuing higher education in project management. Originality/value: To the best of the authors' knowledge, this is one of the first empirical studies that investigate the requirement of students' previous work experience and reveals its significance in higher project management education.